Imagining the human: applying the philosophy of religious studies to Jonathan Z. Smith - Fujiwara, Satoko (Religion, 2024)
Distinguishing between philosophy of religious studies as intra-scientific methodological reflection and philosophy of religion as extra-scientific commitment to values, this article demonstrates the benefits of integrating both, applying critical reflection to the latter as well. As a case study, it focuses on Jonathan Z. Smith’s concepts of humanity and history. Smith’s strategic blend of history and morphology aligns with his extra-scientific vision of humanity, which derived not merely from methodological choices but from philosophical reflection. By comparing Smith’s structuralist arguments with Lévi-Straussian structuralism – interpreted as antihumanism – the article reveals that Smith’s humanistic orientation was embedded in North-American social and academic contexts. It thus advocates for a nuanced examination of religious studies’ philosophical underpinnings, suggesting that, without such analysis, the work of even empirical scholars like Smith might be misconstrued.